Do process simulations during episodic future thinking enhance the reduction of delay discounting for middle income participants and those living in poverty? - O’Donnell, Sara (J Behav Decis Mak, 2018)
Two studies examined whether episodic future thinking (EFT; pre-experiencing future events) reduces discounting of future rewards (DD). No studies have investigated whether process simulations (i.e., simulating the process of executing a future event) amplify EFT’s reduction of DD. Study 1 examined the effect of incorporating process simulations into EFT (N = 42, M(age) = 43.27; 91% female, family income = $75,976) using a 2 × 2 factorial design with type of episodic thinking (process, nonprocess/general) and temporal perspective (EFT, episodic recent thinking) as between‐subjects factors. Study 2 replicated Study 1 in a sample of adults living in poverty (N = 36; M(age) = 38.44, 88% female; family income = $25,625). The results of both studies showed EFT reduced DD, but process‐oriented EFT did not amplify the effect of EFT. Our findings suggest the key ingredient in EFT’s effect on DD is self‐projection into the future. This was also the first study to show EFT improves DD in a sample living in poverty.